Grammar Learning Strategies Applied at the Chinese Department of Bina Nusantara University - Yetty Go; Sofi Zhang; Titi Rahardjanti (Humaniora, 2019)
The aims of this research were to investigate the Chinese language learning strategy used among students of Chinese Department class of 2021 Binus University, the relationship between gender and language learning strategy use, the relationship between language learning strategy and learning achievement, and also the language learning strategy used by students with high learning achievement in the subject of Grammar. This research used Oxford’s language learning strategy questionnaire that was “Strategy for Language Learning (SILL)” to investigate the students’ language learning strategy. This research finds out that the language learning strategy employed by the most students are metacognitive strategy and strategy to be used by high learning achievement students in grammar subject are also metacognitive strategy. It also finds out that female students use more language learning strategies compared to male students, although the difference is not too significant. Results of Pearson Correlation’s test indicate no significant relationship between the students’ language learning strategy and learning achievement. This research shows that there is no dominant language learning strategy used by Chinese Literature students.